Az Európai Unió intézményinek szerepe a közös kül-és biztonságpolitika alakulásában - Pintér Olivér (2005)
The purpose of writing this article was to show the role of the EU institutions on the field of the Common Foreign and Security Policy (CFSP). First we made distinction between the CFSP and the external relations of the EU, we presented that there is an effort in the Treaty of the Constitution to make these two fields common under the direction and responsibility of the Union Minister for Foreign Affairs. Shortly we looked through the beginning of the cooperation among the member states, we displayed the strongholds and weaknesses of the European Political Cooperation (EPC). The Treaty of Maastricht brought a great change on the field of the EPC. The Chapter V of the Treaty created the CFSP, cleared the role of the different European institutions. The Treaties of Amsterdam and Nizza didn't brought a breakthrough, perhaps the implements of the CFSP were cleared. Also a new institution appeared in the Treaty of Amsterdam: Ms./Mr. CFSP, whose main task is to represent the EU to third persons. If the member states accepted the Treaty of Constitution, the CFSP would be laid down on a new foundation.
Keywords: Társadalomtudományok; Politikatudomány